Belowground Biodiversity: AM Fungi Research Trends in Maharashtra - Sarwade, Prakash; Gaisamudre (Sarwade), Kavita Narayan; Bhise, Damaji Shankar; Gaikwad, Rajesh Shrirangrao (Plantae Scientia, 2025)
Arbuscular mycorrhizal (AM) fungi are ubiquitous soil microorganisms that form symbiotic associations with most terrestrial plants, playing a crucial role in nutrient uptake, stress tolerance, and soil health. Maharashtra, with its diverse agroecological zones and soil types, provides a unique opportunity to study the diversity, distribution, and functional roles of AM fungi. This review synthesizes research on AM fungi in Maharashtra, focusing on their ecological significance, biotechnological applications, and future research directions. Surveys across the state have identified over 40 AM fungal species, with genera such as Glomus, Acaulospora, and Gigaspora being predominant. These fungi have been isolated from a wide range of crops and native tree species. Field inoculation studies demonstrate the efficacy of AM fungi in improving crop yield (10–40%), enhancing nutrient uptake, and mitigating biotic and abiotic stresses. Integration of AM fungi with other biofertilizers, such as Rhizobium and phosphate-solubilizing bacteria, has shown synergistic effects on crop productivity and soil fertility. Despite the promising results, AM fungi research in Maharashtra faces challenges, including methodological limitations, short-term studies, and geographical gaps. Future research should focus on molecular and metagenomic approaches, climate change interactions, indigenous knowledge integration, and policy support for widespread adoption. By harnessing the potential of AM fungi, Maharashtra can develop sustainable and resilient agroecosystems that address pressing agricultural and environmental challenges.